The effect of dietary nutrients on osteochondrosis in swine and evaluation of serum biomarkers to predict its occurrence - Frantz, Nolan Zebulon (Kansas State University, 2008)
Four experiments using 350 pigs were conducted to determine the effects of dietary nutrients on the incidence of osteochondrosis (OC) and to evaluate the use of biomarkers to predict its occurrence in growing-finishing pigs. The first experiment was conducted to evaluate the potential of dietary ingredients with known functions in cartilage and bone metabolism on incidence of OC in pigs (PIC 327 × 1050, initially 39 kg). Results suggest that pigs fed high levels of added copper and manganese, silicon, methionine and threonine, or proline and glycine had reduced OC severity scores. A second experiment evaluated other dietary ingredients that may impact OC as well as with or without ractopamine HCl (PIC 327 × 1050, initially 47 kg). Results suggest that feeding a combination of added methionine, manganese, proline, and glycine or added silicon can numerically reduce OC severity scores compared to pigs fed a standard corn-soybean meal based diet. Feeding ractopamine HCl did not affect the incidence or severity of OC. A third experiment was conducted to evaluate the effect of dietary lysine concentration with or without the addition of high methionine, manganese, and copper in a 3 × 2 factorial arrangement in growing-finishing pigs (PIC 327 × 1050, initially 41 kg). Results suggest that increasing dietary lysine concentrations increased the severity of OC. Furthermore, feeding additional methionine, manganese, and copper reduced OC severity scores. A fourth experiment was conducted to determine the usefulness of ten different biomarkers of cartilage and bone metabolism to predict the incidence of OC and the correlation of individual markers with the severity of OC. Results suggest that measuring serum C-propeptide of type II collagen (CPII) will predict animals with OC, as gilts with a two-fold increase in CPII are 97 times more likely to have OC. As well, serum collagen type II carboxy-terminal 3/4 long fragment (C2C) explained 49% of the variation in OC severity scores. The results of these experiments suggest that feeding added copper, manganese, methionine, silicon, or proline and glycine may reduce OC severity scores in pigs, while measuring biomarkers CPII and C2C can aid in determining animals with OC.
Keywords: Osteochondrosis; Biomarkers; Swine; Cartilage; Nutrition; Agriculture, Animal Culture and Nutrition (0475)